2019
DOI: 10.7150/jca.31345
|View full text |Cite
|
Sign up to set email alerts
|

GPC6 Promotes Cell Proliferation, Migration, and Invasion in Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a highly metastatic tumor that occurs frequently in Southeast Asia, particularly including southern China. Epstein-Barr virus infection is well established as a primary cause of NPC; nevertheless, the mechanisms underlying NPC pathogenesis remain largely unknown. In our previous study, we conducted whole-genome sequencing to screen for genomic variations that were associated with NPC. Of the resultantly identified variations, glypican-6 (GPC6), was shown, for the first time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…Studies have suggested that patients with the BRAF V600E mutation should be overtreated to some extent [47], because BRAF mutations are an independent risk factor for lymph node metastasis and are closely related to tumor size and invasiveness [48][49][50][51][52][53][54][55][56][57]. Both the clinical studies and the basic medical studies performed here suggest that the presence of the BRAF mutation may lead to a decrease in the efficacy of iodine-131 treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have suggested that patients with the BRAF V600E mutation should be overtreated to some extent [47], because BRAF mutations are an independent risk factor for lymph node metastasis and are closely related to tumor size and invasiveness [48][49][50][51][52][53][54][55][56][57]. Both the clinical studies and the basic medical studies performed here suggest that the presence of the BRAF mutation may lead to a decrease in the efficacy of iodine-131 treatment.…”
Section: Discussionmentioning
confidence: 72%
“…One mechanism is to connect linearly distant loci with proteins, such as CTCF. In the other mechanism, for the topologically associated domain (TAD) scaffold, contact between the promoter and enhancer can coordinate the regulation of gene expression [75,76]. Promoter-enhancer competition between PVT1 and MYC, described as follows, mainly occurs in the TAD.…”
Section: Promoter-enhancer Competition Between Pvt1 and Mycmentioning
confidence: 99%
“…Although NPC is sensitive to radiotherapy with adjuvant chemotherapy (Ge et al ., 2020; He et al ., 2018; Tang et al ., 2018a), most NPC patients often have metastases at the time of diagnosis. Hence, the prognosis of these patients is poor (Fan et al ., 2019b; Peng et al ., 2019; Ren et al . 2020; Wang et al ., 2019a; Wei et al ., 2018a,b; Xiong et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%